(untitled) (The Research of Medical Science Review, 2025)
Despite the fact that Pakistan is considered a ticking time bomb of HIV/AIDS, the general population in the country still lacks basic information about HIV/AIDS and is rather surrounded by various myths and misconceptions. The lack of accurate information about HIV/AIDS contributes to the perpetuation of stigma. Misconceptions particularly about the modes of transmission and prevention fuel prejudice and fear, leading to the stigmatization of affected individuals and their families. The stigma not only affects the psychological well being but also hampers efforts to promote HIV/AIDS testing and treatment services. Present study employed cross sectional research design to explore the stigma associated with HIV/AIDS in general population in Lahore. None probability convenient sampling technique was used to collect data from 433 individuals. Majority lacked important information related to HIV/AIDS and revealed to have strong stigma against HIV/AIDS. The results also indicated different patterns of associations across age, gender, levels of HIV knowledge and interaction with a HIV/AIDS positive person.